Ready to Eat Food Perception, Food Preferences and Food Choice: Exploring the relationship between food perception, preferences, and choice in ready-to-eat foods (Journal of Advances and Scholarly Researches in Allied Education, 2022)
One of a person's essential necessities is nutrition. It is necessary for both a healthydevelopment and the regular operation of the body's organs. Food that has been packed on the premiseswhere it is being sold and is ready to eat is referred to as ready-to-eat food. It is food that has beenexposed or offered for sale without further cooking or preparation. Increasingly more consumers arebecoming interested in RTE snacks because of its practicality, worth, attractiveness, flavor, and texture.The link between food perception, preferences, and food choice is discussed in this essay. Our first goalis to identify and highlight the variables that influence how we perceive and choose foods. Theresearcher provides examples of the many variables influencing our choices for ready-to-eat foods.